Synthesis of N-aryl beta-amino alcohols by trifluoroacetic acid promoted multicomponent coupling of aziridines, arynes, and water - Roy, Tony; Baviskar, Dnyaneshwar R.; Biju, Akkattu T. (Journal of Organic Chemistry, 2015)
A transition-metal-free, three-component coupling involving N-substituted aziridines, arynes, and water promoted by trifluoroacetic acid (TFA) has been reported. The reaction furnished medicinally important N-aryl beta-amino alcohol derivatives in moderate to good yields. In addition, the use of azetidines in this reaction afforded N-aryl gamma-amino alcohol derivatives.